Divergence and Convergence of Cerebral Ischemia Pathways Profile Deciphers Differential Pure Additive and Synergistic Mechanisms - Wei, Penglu; Wang, Pengqian; Li, Bing; Gu, Hao; Liu, Jun; Wang, Zhong (Frontiers in Pharmacology, 2020)
Aim: The variable mechanisms on additive and synergistic effects of jasminoidin (JA)-Baicalin (BA) combination and JA-ursodeoxycholic acid (UA) combination in treating cerebral ischemia are not completely understood. In this study, we explored the differential pure mechanisms of additive and synergistic effects based on pathway analysis that excluded ineffective interference. Methods: The MCAO mice were divided into 8 groups: sham, vehicle, BA, JA, UA, Concha Margaritifera (CM), BA-JA combination (BJ) and JA-UA combination (JU). The additive and synergistic effects of combination groups were identified by cerebral infarct volume calculation. The differentially expressed genes based on a microarray chip containing 16,463 oligoclones were uploaded to GeneGo MetaCore software for pathway analyses and function catalogue. The comparison of specific pathways and functions crosstalk between different groups were analyzed to reveal the underlying additive and synergistic pharmacological variations. Results: Additive BJ and synergistic JU were more effective than monotherapies of BA, JA and UA, while CM was ineffective. Compared with monotherapies, 43 pathways and 6 functions were found uniquely in BJ group, with 33 pathways and 3 functions in JU group. We found 6 overlapping pathways and 6 overlapping functions between BJ and JU groups, which mainly involved central nervous system development. Thirty-seven specific pathways and 10 functions were activated by additive BJ, which were mainly related to cell adhesion and G-protein signaling; and 27 specific pathways and 3 functions of synergistic JU were associated with regulation of metabolism, DNA damage and translation. The overlapping and distinct pathways and functions may contribute to different additive and synergistic effects. Conclusion: The divergence pathways of pure additive effect of BJ were mainly related to cell adhesion and G-protein signaling, while the pure synergistic mechanism of JU depended on metabolism, translation and DNA damage. Such a systematic analysis of pathways may provide an important paradigm to reveal the pharmacological mechanisms underlying drug combinations.